UNCONSCIOUS BIAS IN THE WORKPLACE - Karomat, Kilicheva (Researchparks Publishing, 2023)
The elemental definition of bias is “an error in decision-making.” Unconscious biases are prejudices humans have but are unaware of. They are mental associations based on social norms and stereotypes. There is a reason it is called unconscious bias. It is because hard-wired biases operate at a level that is beneath conscious awareness. Even if it is believed a person is being fair and objective, stereotypes may still be influencing opinions - without any awareness of it. Subsequently, such oblivious inclinations may create unfair disadvantages within organizations. Thus, the objective of this paper is to review prior studies to analyze the nature of unconscious bias in the workforce and to propose a possible intervention to manage it.